Molecular profile and cell cycle in mcf-7 cells resistant to cisplatin and doxorubicin - Lukyanova, N.Yu.; Rusetskya, N.V.; Tregubova, N.A.; Chekhun, V.F. (Experimental Oncology, 2009)
Aim: To compare ultrastructure, phenotypic profile and cell cycle progression ofMCF-7 human breast cancer cells and MCF7 sublines resistant to cisplatin (MCF-7/DDP) and doxorubicin (MCF-7/DOX). Methods: MTT-test, immunocytochemistry, flow cytometry, electron microscopy. Results: The development of drug resistance to cisplatin and doxorubicin in MCF-7 cells upon the culturing of the initial cells with the raising concentrations of cytostatics was accompanied by the increase in cells adhesion, the increasing differentiation grade and the loss of steroid hormone receptors. Besides, it was shown that antiapoptotic mechanisms (decrease ofBcl-2 expression) and intracellular glutathione detoxifying system are involved in the process of cisplatin resistance development inMCF-7 cells. Atthe same time, P-glycoprotein overexpression in cells resistant to doxorubicin suggests MDR-dependent mechanism. Both doxorubicin- and cisplatin-resistant cells are characterized by the changes in the expression of several cell cycle regulators — Ki-67, cyclin D1, pRb and р21). Conclusion: The long-time culture of MCF-7 cells with cytostatic drugs results in the decreased cyclin D1, pRb, and Ki-67 expression and increased р21 expression with the increasing differentiation grade of the resistant cells. The underlying mechanisms of resistance to cisplatin and doxorubicin in MCF-7 cells may be different.